Phototherapy In The Digital Age: Transformations, Approaches, And Relevance In Contemporary Mental Health Practice. - Tanto Trisno Mulyono; Tresna Wiwitan (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2026)
Phototherapy, which includes both phototherapy and therapeutic photography, represents a visual-based psychological intervention that utilizes photographic images as tools for emotional expression, reflection, and meaning construction. The rapid expansion of digital technology has reshaped this approach through the widespread use of smartphones and visual-oriented social media platforms, embedding image production into everyday life. This study aims to examine the theoretical foundations of phototherapy, identify its primary modalities, explore its applications across contexts, and evaluate its relevance in contemporary mental health practice. This research applied a systematic literature review with a narrative synthesis approach. A total of 75 articles were identified through database searches in Scopus, PubMed, PsycINFO, and Google Scholar. All selected studies met predefined inclusion criteria, covering publications between 1983 and 2023 related to photography-based interventions in mental health. The analysis focused on patterns across theoretical perspectives, intervention types, and application settings. The findings indicate that phototherapy is supported by strong interdisciplinary foundations, including semiotics, neuroscience, and memory theory, which explain how images facilitate emotional processing. Various modalities such as projective techniques, self-portrait, re-enactment, and photovoice demonstrate flexibility across clinical, educational, and community contexts. Digital transformation enhances accessibility and participation, allowing phototherapy to extend beyond traditional therapeutic settings. At the same time, the digital environment introduces ethical challenges related to privacy, ownership, and emotional safety. These findings highlight the importance of integrating technological innovation with ethical awareness and culturally responsive practices in the development of phototherapy